Conjuntos minimais de sistemas lineares por partes - Moraes, Jaime Rezende de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The main goal of this thesis is to find periodic solutions of non–smooth systems. Our contribution in this thesis is related to the study of piecewise linear vector fields, singularly perturbed non–smooth systems and cubic polynomial differential systems in R2 with centers. We study piecewise linear planar vector fields (PWL). We suppose that the equilibrium points are saddle or focus. We establish a correspondence between the PWL vector fields and vectors formed by some of the following parameters: sets on (crossing, sliding or escaping), kind of equilibrium (real or virtual), intersection of the separatrices with , stability and orientation of the focus. Such vectors are called configurations. We reduce the number of the configurations by an equivalent relation and we analyze for which configurations the corresponding PWL vector fields can have or not closed sliding poly-trajectories. For the singularly perturbed non–smooth systems we study two classes of non–smooth singular perturbation problems: with one critical manifold and with two critical manifolds. For the first class we give sufficient conditions for the persistence of closed poly–trajectories. For the second class we give conditions for persistence of equilibrium points. For the cubic polynomial differential systems in R2 with centers we study the maximum number of limit cycles that bifurcate from some families of planar polynomial differential systems of degree 3 with rational first integrals of degree 2 when they are perturbed inside the classes of all cubic polynomial differential systems

O objetivo geral dessa tese é buscar soluções periódicas de sistemas não–suaves. Nossa contribuição nesta tese está relacionada ao estudo de campos de vetores lineares por partes, sistemas não–suaves singularmente perturbados e sistemas diferenciais polinomiais cúbicos em R2 que possuem centros. Estudamos campo de vetores planares lineares por partes (PWL). Supomos que os pontos de equilíbrio são do tipo sela ou foco. Estabelecemos uma correspondência entre os PWL e vetores formados por alguns parâmetros: conjuntos em (costura, deslize ou escape), equilíbrio (real, virtual), interseção das separatrizes com , estabilidade e orientação do foco. Chamamos esses vetores de configuração. Reduzimos o número de configuração por uma relação de equivalÊncia e estudamos quais poderiam ter poli–trajetórias fechadas de deslize. Para os sistemas não–suaves singularmente perturbados estudamos duas classes de problemas de perturbação singular não–suave: com uma variedade crítica e com duas variedades críticas. Para a primeira classe damos condições suficientes para persistência de poli–trajetórias fechadas. Para a segunda estudamos a persistência de pontos de equilíbrio. Para os sistemas diferenciais polinomiais cúbicos em R2 que possuem centros estudamos o número máximo de ciclos limites que podem bifurcar de algumas famílias de sistemas diferenciais planares polinomiais de grau 3, com integrais primeiras racionais de grau 2, quando eles são perturbados dentro da classe de todos os sistemas polinomiais diferenciais ...
Keywords: Matemática; Equações diferenciais; Ciclo limite; Sistemas lineares; Differential equations